(untitled) (Research, Society and Development, 2023)
Objective: To outline the epidemiological profile of Hospitalizations for Primary Care Sensitive Conditions (ICSAP) in adults and elderly people, at the Hospital Universitário Alcides Carneiro (HUAC) in Campina Grande, Paraíba, Brazil. Method: This is a cross-sectional study carried out with a sample of adults and elderly people corresponding to the total number of hospitalizations that occurred during the data collection period. The outcome of the study was “Admission for Primary Care Sensitive Conditions – ICSAP”, obtained from the clinical diagnoses present in the Hospital Admission Authorization (AIHs) and/or Medical Records. The independent variables were: sociodemographic conditions; the attributes of Primary Health Care (PHC); the trajectory of care. Data collection was done through interviews and a standardized questionnaire. Descriptive and inferential statistical analyzes were used. Results: Among 196 hospitalizations evaluated, 47 (24.0%) were classified as ACSC. Among the demographic variables, only employment status was associated with ACSC (p<0.05). Medium and High Complexity were mainly responsible for referrals to hospital admission. Accessibility was compromised in both groups studied. The average time between the first symptoms and the first visit to the health service, as well as in relation to hospitalization, showed significant differences between the groups. Conclusions: the results show that sociodemographic variables, PHC attributes and the journeys taken by the family to hospital admission are important factors in the assessment of ACSC.